The growth response of Eucalyptus grandis x e. camaldulensis to salt stress, ectomycorrhizae and endomycorrhizae double colonisation - Hengari, Simeon Ngaitungue (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2007.